The Attributes of Educators in Islam (Analysis of the Book of At Tarbiyah Al Amaliah by KH Imam Zarkasyi): Sifat-Sifat Pendidik dalam Islam (Analisis Kitab At Tarbiyah Al Amaliah Karya KH Imam Zarkasyi) - Mappanyompa, Mappanyompa; Muhlis, Muhammad; Sahwan, Sahwan; Saprun, Saprun (Universitas Muhammadiyah Sidoarjo, 2024)
This study focuses on exploring Islamic values, the characteristics of educators, and the concept of Islamic education through the analysis of the book